The Effect of Social Support on Stress in Daughters-in-Law Living with In-Laws - Juniarti, Riska; Arsi, Qisthina; Sumarni, Novi (Lafadz Jaya Publisher, 2024)
Marriage often requires couples to make significant adjustments, including co-residing with in-laws. This study explores the relationship between social support and stress among 97 daughters-in-law living with their in-laws. Using purposive sampling, we adapted and modified measurement tools: Mayanti (2019) for social support (reliability coefficient: 0.952, 28 valid items) and Shabrina (2017) for stress (reliability coefficient: 0.926, 39 valid items). Regression analysis revealed a significant negative relationship between social support and stress (p = 0.000, β = -0.489). Social support accounted for 42.8% of stress variance, leaving 57.2% attributed to other factors. Findings indicate that high social support reduces stress levels, whereas low social support increases stress. Among respondents, 54.6% experienced high stress, while 45.4% reported low stress. This study emphasizes the critical role of social support in mitigating stress for daughters-in-law cohabiting with in-laws.